Assessment of remineralization via measurement of dehydration rates with thermal and near-IR reflectance imaging. Issue 8 (August 2015) - Lee, Robert C.; Darling, Cynthia L.; Fried, Daniel
Abstract Objectives Previous studies have demonstrated that the optical changes due to the loss of water from porous lesions can be exploited to assess lesion severity with QLF, thermal and near-IR imaging. Since arrested lesions are less permeable to water due to the highly mineralized surface layer, changes in the rate of water loss can be related to changes in lesion structure. The purpose of this study was to investigate whether the rate of water loss correlates with the degree of remineralization and whether that rate can be measured using thermal and near-IR reflectance imaging. Methods Artificial bovine enamel lesions (n = 30) were prepared by immersion in a demineralization solution for either 8 and 24 h and they were subsequently placed in an acidic remineralization solution for different periods. The samples were dehydrated using an air spray for 30 s and surfaces were imaged using a thermal camera and an InGaAs camera at 1300–1700 nm wavelengths. Results The area enclosed by the time–temperature curve, ΔQ, from thermal imaging showed significant differences (P < 0.05) between the lesion window and other windows. Near-IR reflectance intensity differences, ΔI, before and after dehydration decreased with longer periods of remineralization. Only near-IR reflectance imaging was capable of detecting significant differences (P < 0.05) between the different periods of remineralization. Conclusions This study demonstrated that both thermal and near-IR reflectance imaging were suitable for the detection of remineralization in simulated caries lesions and near-IR wavelengths longer than 1400 nm are well suited for the assessment of remineralization.